The Commercial Face of God: Exploring the Nexus Between the Religious and the Material - Kong, Lily (Institutional Knowledge at Singapore Management University, 1996)
This paper explores the nexus between the cultural and the material by examining the ways in which religion and the economy are integrated in the context of economy-driven Singapore. The mutually constitutive relationships between the cultural and the material are explored through a discussion of the role of the state, capital and religious institutions in pulling together the sacred and the secular. Specifically, the analysis focuses on how the state harnesses religion ideologically in its economic development strategies; how capital harnesses the potential of religion in commercial enterprises in practical terms; and how religious institutions themselves behave as financial institutions. The ways in which individuals deal with these structural forces and the integration of the 'this-worldly' and the 'wholly other' are also discussed, illustrating the intersection between structural forces and individual experiences.